2019
DOI: 10.3390/ijerph16193619
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment in Western China: Demographic Differences and Associations with Mental Health

Abstract: Background: Child maltreatment has become a serious public health and social problem worldwide. However, knowledge regarding the status of child maltreatment in western China is limited. Objective: The objective of this study was to investigate the status of child maltreatment in western China and its relationship with mental health. Participants and setting: The present study evaluated child maltreatment in a sample of 1511 children (Mage = 11.48 years) from western China. Methods: The participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
3
12
1
Order By: Relevance
“…The results were in accord with other studies revealing that the effects of single polymorphism on NSSI and NSSI-related traits (e.g., depression) were always small or negligible [ 33 , 56 ]. Additionally, our results did not show the main effects of child abuse or neglect on NSSI, contrary to some studies [ 57 , 58 , 59 ]. Recent reviews have suggested that the diversity of participants (e.g., gender difference), the existence of mediators [ 16 ], or the type of maltreatment [ 60 ] could contribute to heterogeneity among studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The results were in accord with other studies revealing that the effects of single polymorphism on NSSI and NSSI-related traits (e.g., depression) were always small or negligible [ 33 , 56 ]. Additionally, our results did not show the main effects of child abuse or neglect on NSSI, contrary to some studies [ 57 , 58 , 59 ]. Recent reviews have suggested that the diversity of participants (e.g., gender difference), the existence of mediators [ 16 ], or the type of maltreatment [ 60 ] could contribute to heterogeneity among studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The multinomial logistic regression suggested that demographic characteristics of sex, parental education background, residential home, and family income were related to profile membership. Females were generally less likely than males to be in profiles characterized by higher abuse and neglect, consistent with prior findings whereby boys were more likely to suffer psychologically from abuse and neglect in China (Zhou, Liang, Cheng, Zheng, & Liu, 2019). This is, however, notably in contrast to the general trends of studies sampling Western populations (Witt, Brown, Plener, Brahler, & Fegert, 2017).…”
Section: Demographic Analysis Of Different Patterns Of Psychological Abuse and Neglectsupporting
confidence: 84%
“…These differences may need to further widen under the influence of different political systems and historical-cultural backgrounds. For example, in China, emotional neglect, emotional abuse, and physical abuse are considered effective parenting strategies to control child behaviour, which has resulted in more than half of Chinese children experiencing different types of child maltreatment (Wang, Xing, & Zhao, 2014 ; Zhou, Liang, Cheng, Zheng, & Liu, 2019 ). Meanwhile, individuals prefer to adapt to circumstances rather than seek outward change in Chinese culture (Aubert, Daigle, & Daigle, 2004 ).…”
Section: Introductionmentioning
confidence: 99%